If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(8x + -1) + 2(-9 + 2x) + x = 0 Reorder the terms: -8(-1 + 8x) + 2(-9 + 2x) + x = 0 (-1 * -8 + 8x * -8) + 2(-9 + 2x) + x = 0 (8 + -64x) + 2(-9 + 2x) + x = 0 8 + -64x + (-9 * 2 + 2x * 2) + x = 0 8 + -64x + (-18 + 4x) + x = 0 Reorder the terms: 8 + -18 + -64x + 4x + x = 0 Combine like terms: 8 + -18 = -10 -10 + -64x + 4x + x = 0 Combine like terms: -64x + 4x = -60x -10 + -60x + x = 0 Combine like terms: -60x + x = -59x -10 + -59x = 0 Solving -10 + -59x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -59x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -59x = 0 + 10 -59x = 0 + 10 Combine like terms: 0 + 10 = 10 -59x = 10 Divide each side by '-59'. x = -0.1694915254 Simplifying x = -0.1694915254
| 8a+3a+8=9a-2a-16 | | 25/2 | | -3m-6=5m-3 | | x/100=45/360 | | (3x+10)+(2x)=180 | | 20+4=7+4((-6)+5) | | Log(x^2-1/x)^3 | | (3x)+7=13 | | -6a+3a-13=0 | | 6c+20=4c | | 8z(6y+10z)+80z=0 | | 4x-12-6x+21=-1 | | 2(x-16)=x+5+11 | | 4m-6=3m+11 | | 2x+4y=1104 | | x+2.9=11.6 | | 7x+5y-2y= | | bhg=2x-30whatisx | | f(x)=x^2+10x-16 | | 5(x+7)=3x+47 | | bhg=2x-30 | | 3x+3z=6+8y | | 4x-3=7+3x | | 3cot(x)=1 | | 4x+3=-5+20 | | 64-s= | | -150x+3271567812785361985=5 | | 3/4x-1/4=3/4 | | 7x+4=x-4 | | 5.25m=-73.5 | | 5x+79y=2x+3 | | -5(-7-3x)+7= |